Upaya Peningkatan Hasil Belajar Siswa dengan Menerapkan Model Pembelajaran Kooperatif Tipe The Power of Two pada Pembelajaran Tematik Kelas VI MIN 7 Bandar Lampung Tahun Pelajaran 2021/2022 - Rubbaya, Siti (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2023)
This study aims to describe the increase in student learning outcomes by applying the cooperative learning model of the Power of Two type to thematic learning in class VI MIN 7 Bandar Lampung. This classroom action research uses a research method with the Jhon Elliot model with the stages of planning, action, observation, and reflection. The subjects of this study were students of class VI Al Muiz MIN 7 Bandar Lampung which involved 23 students. The object of research is the results of student learning by applying the cooperative learning model of the Power of Two type. The data was collected using tests and observations. Data analysis used descriptive quantitative data analysis techniques and qualitative data. The results of the study by applying the power of two cooperative learning model in class VI Al Muiz showed that it could improve student learning outcomes. In cycle I, it can be seen from the average test results according to the KKM (75), cycle I increased to 17 students (73.91%) who completed with an average value of 80, and cycle II increased again to 21 students. (91.3%) who completed with an average value of 86.5. From the overall percentage of cycle I and cycle II, student learning outcomes increased.